Pengaruh Penggunaan Tepung Beras Merah Terhadap Kualitas Kimia Sosis Darah Tradisional (Budik): The Effect of Adding Red Rice Flour on the Chemical Quality of Traditional Blood Sausage (Budik) - Yustin Kantur; Bastari Sabtu; Heri Armadianto (Jurnal Peternakan Lahan Kering, 2023)
The purpose of this study, among others, was to determine the addition of red rice flour and sausage ingredients (meat from the head, liver, heart, lungs) on the chemical quality of budik (traditional blood sausage). This study used a completely randomized design (CRD) with four treatments and four replications. Combination treatment of  P0: without red rice flour + sausage ingredients, P1: 2% red rice flour + sausage ingredients, P2: 4% red rice flour + sausage ingredients, P3: 6% red rice flour + sausage ingredients. The data obtained to ascertain differences between treatments, Duncan's test was used after the Analysis Of Variance. The results showed a significant effect (P<0.05) of the addition of brown rice flour on the fat content of the seed and no significant effect (P>0.05) on the content of Protein, Water and Crude Fiber. It was concluded that the addition of brown rice flour affected the fat content of the traditional blood sausage. The lowest fat content was found in the addition of 6% red rice flour, while the levels of protein, water and crude fiber were relatively the same. Tujuan penelitian ini adalah mengetahui penambahan tepung beras merah dan bahan sosis (daging dari bagian kepala, hati, jantung, paru-paru) terhadap kualitas kimia budik (sosis darah tradisional). Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan empat perlakuan dan 4 empat ulangan. Perlakuan kombinasi dari P0: tanpa tepung beras merah + bahan sosis, P1: tepung beras merah 2% + bahan sosis, P2: tepung beras merah 4 % + bahan sosis, P3: tepung beras merah 6% + bahan sosis. Data yang diperoleh untuk memastikan perbedaan antara perlakuan, ujin Duncan digunakan setelah Analysis Of Variance. Hasilnya menunjukkan pengaruh nyata (P<0,05) dari penambahan tepung beras merah terhadap kadar lemak budik serta berpengaruh tidak nyata (P>0,05) terhadap kadar Protein, Air, Serat Kasar budik. Disimpulkan bahwa penambahan tepung beras merah mempengaruhi kadar lemak budik atau sosis darah tradisional. Kadar lemak paling rendah terdapat pada penambahan 6% tepung beras merah, Sedangkan kadar protein, air dan serat kasar relatif sama.